Correction of precipitation measurement for weighing precipitation gauges in a glacierized basin in the Tianshan Mountains - Jia, Yufeng; Li, Zhongqin; Wang, Feiteng; Chen, Puchen (Frontiers in Earth Science, 2023)
The precipitation observation network was constructed in the Urumqi River basin based on the six meteorological stations range from 935m to 4025m. The 30-min precipitation datasets in 2019 at the automatic weather station in the snout of Urumqi Glacier No .1 were used to test the World Meteorological Organization Solid Precipitation Intercomparison Experiment transfer functions. The parameters were recalibrated by the local datasets. Results showed that the transfer functions had a better performance after recalibrating parameters by local data. The root-mean-square error (RMSE) and mean bias decrease by an average of 34% and 42%. The corrected snowfall increased by 14 mm (7%). Then, the new parameters were used in the other two automatic weather station to corrected precipitation. According to the corrected precipitation, the precipitation-altitude relationship of Urumqi River basin was analyzed.